The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s13311-017-0591-2
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Quantitative Proteomics Reveals the New Evidence Base for Traumatic Brain Injury Treated with Targeted Temperature Management

Abstract: This study aimed to investigate the effects of targeted temperature management (TTM) modulation on traumatic brain injury (TBI) and the involved mechanisms using quantitative proteomics technology. SH-SY5Y and HT-22 cells were subjected to moderate stretch injury using the cell injury controller (CIC), followed by incubation at TTM (mild hypothermia, 32°C), or normothermia (37°C). The real-time morphological changes, cell cycle phase distribution, death, and cell viability were evaluated. Moderate TBI was prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…FB23-2 can inhibit the m6A demethylase FTO, and it has been confirmed in leukemia studies that the degree of m6A methylation is reduced after intraperitoneal injection of FTO [33]. In the mNSS experiments, the neurological function of rats after TBI presents a tendency to restore itself, which is in agreement with previous studies [56]. However, the self-healing phenomenon was not found in FB23-2-injected TBI rats, indicating that functional FTO is necessary to repair neurological damage caused by TBI.…”
Section: Discussionsupporting
confidence: 89%
“…FB23-2 can inhibit the m6A demethylase FTO, and it has been confirmed in leukemia studies that the degree of m6A methylation is reduced after intraperitoneal injection of FTO [33]. In the mNSS experiments, the neurological function of rats after TBI presents a tendency to restore itself, which is in agreement with previous studies [56]. However, the self-healing phenomenon was not found in FB23-2-injected TBI rats, indicating that functional FTO is necessary to repair neurological damage caused by TBI.…”
Section: Discussionsupporting
confidence: 89%
“…Using a combination of an in-vitro stretch model, a rat CCI model and CSF from TBI patients, Cheng et al [ 2 ▪▪ ] investigated the influence of hypothermia on response to TBI. The proteomics portion of this study involved an examination of the influence of hypothermia after CCI.…”
Section: Progress To Date In 2018mentioning
confidence: 99%
“…As for TBI, proteomics has been primarily applied to discover new biomarkers [ 41 , 42 ]. In particular, Cheng et al found that targeted temperature management (TTM) prevented TBI-induced neuronal necrosis, neuronal death, and brain edema, and some altered proteins (i.e., plasminogen, antithrombin III, and transthyretin) were identified [ 43 ]. Wu et al detected protein changes in the traumatically injured hippocampus and found that pathways associated with global energy metabolism were significantly downregulated [ 44 ].…”
Section: Introductionmentioning
confidence: 99%